Functional movement screen test during a soccer game in young players - Cavaggioni, L.; Trecroci, A.; Millefanti, A.; Alberti, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: During a soccer match there are many physiological and sport specific parameters that changes from the beginning to the end. It seems that in young soccer players, as well as in adults, there are differences between role position in terms of distance covered , sprinting and high intensity (HI) actions,which are lower in the second half, but with similar HR values. Also specific technique ability is affected, in fact there is a decline of short passing abilities. Many quantitative factors may be involved during a match, however there are few studies related to qualitative aspects and their development during a game. The purpose is to provide available data about using and examining the effect of a match on general quality of movement in young football players. METHODS: Eight male regional-level football players (15±1 yrs, 57±2 kg, 169±1.5 cm, 20±1 kg/m2) were recruited. Functional Movement Screen (FMS) underwent to all players in order to obtain an evaluation of the general quality of movement before and after an official game. FMS consisted on deep squat-in line lunge-hurdle step-shoulder mobility-active straight leg raise-push up and rotary stability. Due to the rank-order nature of the data, Wilcoxon Signed Rank test were used to examine differences in the FMS scores. RESULTS: Pre to post differences in the movement patterns were pointed out by FMS single scores: All players performed worse on deep squat, in line lunge, active straight leg raise and rotary stability compared to the beginning of the match (p<.05). Significant differences were reported also in the composite score:61.9 pre Vs. 51 post match. Regional level soccer players showed different quality in the squatting, the lunging, the hip mobility and dynamic motor control patterns. CONCLUSIONS: Young players can exhibit different qualities of functional movement during a 70 minutes match. After the game subjects were less balanced during multi-directional movements, presented minor motor control and poor hips mobility. This could be attributed to the match related fatigue which limit not only specific-technical or physiological parameters, but also the execution of basic movement patterns. For a football player, for whom is important to be in balance, to be strong, to have body control and flexibility, indeed the FMS could be an easy strategy to evaluate the quality of movement during the growth period or to introduce specific exercises after training, especially when they are tired.